Controlling as a сompany management concept - Dźwigoł, H. (Економічний вісник Донбасу, 2017)
The author defines contemporary concepts of business management. It perceives it as a system for planning, controlling, collecting and processing information. Based on his own experience in business practice, and with the theoretical background in management science, he suggests the implementation of a modern management process taking into account the principles of control. The author presented advantages of the implemented controlling (viewed from the methodological point of view), with a consideration given to a series of analysis- and project-related works that were defined in three stages.